Increasing Students’ English Vocabulary by Applying Games and Songs at the Seventh Grade of SMP Negeri 8 Komodo - Aloysia Moto; Junus Ludji Djonga; Armi Reinnati; Sulistyaningsih (JournEEL, 2021)
This research aimed to know whether by applying games and songs can increase students’ vocabulary. It was conducted at seventh grade of SMPN 8 Komodo. Games are a way to relax class routines for fun, games also can make students enthusiastic about playing, sometimes challenging. Songs be trusted to help students in memorizing vocabulary. Memorizing song can be used to increase students’ vocabulary. The students’ responses showed that they were interested in learning vocabulary through using games and songs. It can be seen from the students’ score on vocabulary test which increased from three vocabulary tests given in the Cycle I and Cycle II. In the students’ achievement Cycle I was 57,5 and Cycle II was 77,5. It can be concluded that games and songs have a significant impact on increasing students’ vocabulary number.